Promoting photo-fenton catalytic performance of novel NiZrO3-type perovskite: Optimization with response surface methodology - Kanmaz, Nergiz; Buğdaycı, Mehmet (Elsevier B.V., 2024)
Perovskite type NiZrO3 photocatalysts were synthesized by ball-mill technique and used for tetracycline (TC) degradation. NiZrO3 milled for 6 h (NiZrO3-6h) had significant-99 % photo-Fenton catalytic activity on TC removal It was determined that the characteristic peaks of NiZrO3 with XRD, spherical shaped structures with SEM, no organic peaks in the structure with FTIR, band gap of 4.40 eV with DRS and stable colloids with zeta potential. Response surface methodology (RSM) including Box-Behnken design (BBD) was applied to examine H2O2, Fe2+ and initial TC concentration effects on degradation and it was observed that H2O2 concentration had the highest effect on TC degradation. The photocatalytic efficacy of NiZrO3 could still eliminate 78 % of initial antibiotic molecules after eight-cycle. The application potential for Photo-Fenton assisted NiZrO3-6h was also observed in the degradation of other organic pollutants such as drugs (salicylic acid, ciprofloxacin, ampicillin) and dye (methylene blue, rhodamine-b, orange-II, malachite green, crystal violet). It suggests that the mechanochemically synthesized NiZrO3-6h perovskite could be suitable for its effective use in the photo-Fenton catalytic system.
Keywords: Ball-Milling; NiZrO3; Perovskite; Photo-Fenton; Photocatalysis; Tetracycline